CELORY (Celebrating Local History) Comic Exhibition on Instagram: Conserving Local History Through Project-Based English Learning - Bashori, Muzakki; Fadhila, Qonita; Azmi, Inez Kalyana; Shokheh, Mukhamad; Utama, Nanda Julian (Universitas Negeri Semarang, 2023)
Many local histories in Indonesia remain unnoticed by learners. Learning materials that inform the local histories are generally limited, boring, and do not fit and attract today’s learners, especially those available in English. We investigated the potential of an English as a Foreign Language (EFL) classroom project that promotes and celebrates local histories in Indonesia through (digital) comics. The comics were developed by second-year university students majoring in history (n=156) working in groups of three or four. A total of 51 comics with various themes related to Indonesian local histories were successfully created and exhibited virtually on a designated Instagram account. A questionnaire with a 5-point Likert scale containing 12 statements and two open-ended questions was employed to examine the impact of this project-based learning on students’ understanding and awareness of conserving their local histories through comics. We analyzed the results using SPSS (for quantitative data) and thematic analysis (for qualitative data). Findings indicate that students believe a comic is an interesting medium for learning local history and that local histories in Indonesia need to be promoted via various media, including comics. Future research should investigate the effects of English comics on students’ comprehension of local history in Indonesia and linguistic competence in history-related vocabulary and pronunciation.